2022
DOI: 10.14744/tjtes.2022.00794
|View full text |Cite
|
Sign up to set email alerts
|

Is C-reactive protein–albumin ratio or neutrophil–lymphocyte ratio a better indicator to predict in-hospital mortality in traumatic brain injury?

Abstract: BACKGROUND: Neutrophil-lymphocyte ratio (NLR) and C-reactive protein-albumin ratio (CAR) are simple and objective markers of inflammatory responses. However, there are no studies in the literature evaluating these two markers together in traumatic brain injury (TBI). Therefore, this study aimed to examine whether CAR or NLR is a better biomarker for predicting in-hospital mortality in patients with TBI. METHODS: A total of 257 consecutive patients admitted to the hospit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 25 publications
1
0
0
Order By: Relevance
“…[11] It has been reported that the most common causes of TBI are traffic accidents and falls, and the most common primary diagnoses in patients are subarachnoid hemorrhage and acute subdural hematoma. [12] In our study, consistent with the literature, the most common causes of TBI were falls and traffic accidents, and the most common primary diagnoses were acute subdural hematoma and subarachnoid hemorrhage.…”
Section: Discussionsupporting
confidence: 89%
“…[11] It has been reported that the most common causes of TBI are traffic accidents and falls, and the most common primary diagnoses in patients are subarachnoid hemorrhage and acute subdural hematoma. [12] In our study, consistent with the literature, the most common causes of TBI were falls and traffic accidents, and the most common primary diagnoses were acute subdural hematoma and subarachnoid hemorrhage.…”
Section: Discussionsupporting
confidence: 89%